2015
DOI: 10.1080/02640414.2015.1069379
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-mechanical adjustments to shod versus barefoot treadmill runs in the acute and delayed stretch-shortening cycle recovery phases

Abstract: In habitually shod recreational runners, we studied the combined influence of footwear and stretch-shortening cycle (SSC) fatigue on treadmill running pattern, paying special attention to neuro-mechanical adjustments in the acute and 2-day delayed recovery periods. The SSC exercise consisted of a series of 25 sub-maximal rebounds on a sledge apparatus repeated until exhaustion. The acute and delayed functional fatigue effects were quantified in a maximal drop jump test. The neuro-mechanical adjustments to fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This topic is of interest to athletes and coaches since many runners continue to run, despite experiencing significant DOMS. Consistent with previous literature (Chen et al, 2007;Chen et al, 2009;Dutto & Braun, 2004;Morio, Nicol, Barla, Barthelemy, & Berton, 2012;Morio, Sevrez, Chavet, Berton, & Nicol, 2016;Satkunskiene et al, 2015;Tsatalas et al, 2013), knee flexion ROM was reduced in the presence of knee extensor DOMS. This reduction in flexion ROM appears to be the result of a reduced knee flexion at foot contact, since peak knee flexion was unchanged.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This topic is of interest to athletes and coaches since many runners continue to run, despite experiencing significant DOMS. Consistent with previous literature (Chen et al, 2007;Chen et al, 2009;Dutto & Braun, 2004;Morio, Nicol, Barla, Barthelemy, & Berton, 2012;Morio, Sevrez, Chavet, Berton, & Nicol, 2016;Satkunskiene et al, 2015;Tsatalas et al, 2013), knee flexion ROM was reduced in the presence of knee extensor DOMS. This reduction in flexion ROM appears to be the result of a reduced knee flexion at foot contact, since peak knee flexion was unchanged.…”
Section: Discussionsupporting
confidence: 92%
“…It appears that risk of certain injuries may not be any different since frontal and transverse plane joint biomechanical variables previously associated with running injuries are unaltered when knee extensor DOMS is present. Morio et al (2016) observed an increase in ankle eversion ROM during shod running at 48 h following exhaustive SSC. The authors suggest that the proprioceptive perturbations from exhaustive SSC may have affected sense of joint position and movement.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Participants tested three shoe conditions in a randomized order: shoe drop of 0, 6 and 10 mm ( D 0 , D 6 and D 10 , respectively) with an average thickness of the sole of 25 mm for all conditions and a shoe weight of 246, 242 and 236 g, respectively. For each shoe condition, participants were first asked to run for 4 min on a treadmill at their preferred running speed in order to stabilize the shoe properties (Divert, Baur, Mornieux, Mayer, & Belli, 2005) and adapt and stabilize their running pattern to the shoe condition (Morio, Sevrez, Chavet, Berton, & Nicol, 2016). Subsequently, they performed five trials at the same speed.…”
Section: Methodsmentioning
confidence: 99%